Perancangan User Interface dan User Experience Sistem Informasi E-learning Menggunakan Design Thinking - Devi Karlina; Dwi Rosa Indah (Maranatha University Press, 2022)
The COVID-19 pandemic has caused various activities to be shifted online, one of which is learning activities at school. Because they don't have their own e-learning information system, online learning activities at SMA Tunas Bangsa Palembang utilize various media such as Classrooms to create classes, Google Forms to fill absences, and YouTube to deliver material. Lots of media and there are still perceived shortcomings related to the features of the media used cause the implementation of learning activities become less effective and efficient. Thus, to provide comfort and convenience in these learning activities, an e-learning information system user interface and user experience (UI/UX) design is required. This study uses design thinking as a method that has 5 stages, starting with problem exploration (empathize) to testing the solution design prototype (test). Prototype testing is carried out using the usability testing method, using task scenarios and the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) questionnaires. The results of usability testing using SUS task scenarios and questionnaires include aspects of learnability and efficiency of teacher and student user groups, namely 100% and 0.04 goals/sec, for teacher user satisfaction aspects is 93 with grade scale